CcpA affects expression of the groESL and dnaK operons in Lactobacillus plantarum - Castaldo, Cristiana (BioMed Central, 2006)
BACKGROUND: Lactic acid bacteria (LAB) are widely used in food industry and their growth performance is important for the quality of the fermented product. During industrial processes changes in temperature may represent an environmental stress to be overcome by starters and non-starters LAB. Studies on adaptation to heat shock have shown the involvement of the chaperon system-proteins in various Gram-positive bacteria. The corresponding operons, namely the dnaK and groESL operons, are controlled by a negative mechanism involving the HrcA repressor protein binding to the cis acting element CIRCE. RESULTS: We studied adaptation to heat shock in the lactic acid bacterium Lactobacillus plantarum. The LM3-2 strain, carrying a null mutation in the ccpA gene, encoding the catabolite control protein A (CcpA), showed a lower percent of survival to high temperature with respect to the LM3 wild type strain. Among proteins differentially expressed in the two strains, the GroES chaperon was more abundant in the wild type strain compared to the mutant strain under standard growth conditions. Transcriptional studies showed that class I heat shock operons were differentially expressed upon heat shock in both strains. Indeed, the dnaK and groESL operons were induced about two times more in the LM3 strain compared to the LM3-2 strain. Analysis of the regulatory region of the two operons showed the presence of cre sequences, putative binding sites for the CcpA protein. CONCLUSION: The L. plantarum dnaK and groESL operons are characterized by the presence of the cis acting sequence CIRCE in the promoter region, suggesting a negative regulation by the HrcA/CIRCE system, which is a common type of control among the class I heat shock operons of Gram-positive bacteria. We found an additional system of regulation, based on a positive control exerted by the CcpA protein, which would interact with cre sequences present in the regulatory region of the dnaK and groESL operons. The absence of the CcpA protein results in a lower induction of the chaperon coding operons, with a consequent lower percent of survival of the LM3-2 mutant strain population with respect to the wild type when challenged with a heat insult.